Racial disparities in TAVR outcomes in patients with cancer - Kotloff, Ethan D.; Desai, Yash; Desai, Rohan; Messner, Christopher; Gnilopyat, Sergey; Sonbol, Mark; Aljudaibi, Abdullah; Tarui, Ai; Ives, Juwan; Shah, Nisarg; Vaish, Ishan; Chahal, Diljon; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Advances in cancer therapies and improvement in survival of cancer patients have led to a growing number of patients with both cancer and severe aortic stenosis (AS). Transcatheter aortic valve replacement (TAVR) has been shown to be a safe and effective treatment option for this patient population. There are established racial disparities in utilization and outcomes of both cancer treatments and TAVR. However, the effect of race on TAVR outcomes in cancer patients has not been studied. Objectives The purpose of this study was to investigate racial disparities in outcomes of TAVR in cancer patients. Methods 343 patients with cancer who underwent TAVR at a single center over a 6-year period were included in the study. The primary endpoint was a composite of 1-year mortality, stroke, and bleeding. Secondary outcomes included individual components of the primary endpoint as well as 30-day mortality, structural complications, vascular access complications, and conduction system complications. Outcomes were compared between black and white patients by comparing incidence rates. Results Baseline characteristics including age, sex, BMI, medical comorbidities, STS score, and echocardiographic parameters were similar between races, aside from significantly higher rates of CKD (50.0% vs. 26.6%, p=0.005) and ESRD (18.4% vs. 4.9%, p=0.005) in black compared to white cancer patients. There was a trend toward worse outcomes in black cancer patients with regard to a composite endpoint of 1-year mortality, stroke, and major bleeding (35.7% vs. 22.6%, p=0.095), primarily driven by higher 1-year mortality (31.0% vs. 17.6%, p=0.065). 30-day mortality was twice as high in black cancer patients than in white cancer patients (4.8% vs. 2.3%, p=0.018). Conclusions There is a trend toward worse TAVR outcomes in black cancer patients, with higher periprocedural complication rates and mortality, compared to white cancer patients. Further studies are needed to elucidate the structural, socioeconomic, and biological factors that contribute to racial differences in outcomes.